A new copolymer based on a D–π–A or D–A–π repeat unit for polymer solar cells employing non-halogenated solvents. Issue 20 (11th May 2018) - Xin, Yue; Zeng, Guang; Zhang, Jidong; Zhao, Xiaoli; Yang, Xiaoniu
Abstract : A new copolymer based on a D–π–A/D–A–π repeat unit was designed to improve solubility and device performance in non-halogenated solvents. Abstract : It's a challenge to prepare high-performance polymer solar cells (PSCs) employing non-halogenated solvents due to the poor solubility of conjugated polymers. Here, a new region-random copolymer, in contrast to traditional polymers featuring a D–A or D–π–A–π backbone, is synthesized and fully characterized. By polymerizing ffBT-T (π–A) units with BDT (D) units, the resultant polymer PBDT-ffBT-T (P1T) with repeat units of D–π–A or D–A–π exhibits superior solubility in non-halogenated solvents and outperforms its traditional analogues with the highest performance of 8.53% when processed from anisole. Importantly, the optimal device performance is attained with an active layer thickness of over 200 nm and shows no batch-to-batch difference, implying its compatibility with printing technology. Our results demonstrate that this simple chemical modification for copolymers may significantly benefit the development of PSCs using environmentally friendly solvents.